Incidence of and risk factors for pancreatic cancer in chronic pancreatitis: A cohort of 1656 patients. Issue 11 (November 2017) - Hao, Lu; Zeng, Xiang-Peng; Xin, Lei; Wang, Dan; Pan, Jun; Bi, Ya-Wei; Ji, Jun-Tao; Du, Ting-Ting; Lin, Jin-Huan; Zhang, Di; Ye, Bo; Zou, Wen-Bin; et al.
Abstract: Background: Risk of pancreatic cancer may increase in chronic pancreatitis patients. Aims: This study aimed to identify the incidence of and risk factors for pancreatic cancer in chronic pancreatitis patients. Methods: Chronic pancreatitis patients admitted to our center from January 2000 to December 2013 were enrolled. Cumulative rates of pancreatic cancer and survival rates were calculated. The standardized incidence ratio was calculated based on the pancreatic cancer incidence in general population of China. Risk factors for pancreatic cancer were identified. Results: In a total of 1656 patients, the median follow-up duration was 8.0 years. Pancreatic cancer was detected in 21 patients (1.3%). The expected number of cases of pancreatic cancer was 1.039, yielding a standardized incidence ratio of 20.22. The standardized incidence ratios for patients with a >60 pack-year smoking history were much higher (145.82). Two risk factors for pancreatic cancer were identified: age at the onset of chronic pancreatitis (hazard ratio, 1.05) and a >60 pack-year smoking history (hazard ratio, 11.83). Conclusion: The risk of pancreatic cancer is markedly increased in chronic pancreatitis patients compared with the general population, especially in patients with an older age at onset and a >60 pack-year smoking history. The high-risk populations were suggested to be followed up closely.